„Kao misnik” i „kao Turci iz Smail-age”. A Function of Food in the Modern and Postmodern Narration of The Better Half of Courage by Ivan Slamnig - Pieniążek-Marković, Krystyna (Poznańskie Studia Slawistyczne, 2017)
In the novel entitled The Better Half of Courage, Ivan Slamnig elaborates on two types of narrative namely, a traditional internal story derived from the poetics of realism and a postmodern frame story streaked with the elements of the jeans prose. In the article, culinary motifs presented in both narratives are taken into consideration in order to expose their function in Slamnig’s novel. The article also tries to answer the question whether the dietary code is subordinated to the both forms of discourse. The analysis of the culinary themes reveals a process of braking off with tradition in the so-called traditional narrative, and attempts of retaining tradition in the postmodern narrative. In consequence, an apparently traditional modern pilgrim, who does not respect the order of traditional rituals and remains cautious in his consumption behaviour, turns out to be condemned to painful results of his choices while a postmodern vagrant as an unfulfilled consumer-glutton keeps drawing from tradition as well as from the present day what provides him with various pleasures. Furthermore, the analysis of the culinary code of the novel allows the authoress to confirm a thesis on the presence of postmodern effects in the both “parts” of the novel.